2014
DOI: 10.1051/shsconf/20141101014
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Adaptive Reuse of Heritage Shop Houses for Sleep Lodging in Malaysia: Fulfilment of Conservation Guidelines

Abstract: Abstract. This study focuses on the compliance of adaptive reuse of historic shop houses for sleep lodging with reference to the Guidelines for Conservation Areas and Heritage Buildings by Majlis Perbandaran Pulau Pinang (MPPP). Through this research, awareness towards the compliance of building conservation guidelines for heritage shop houses will be clarified accordingly. The goal of this study is to determine and extract vital clauses and components of Guidelines for Conservation Areas and Heritage Building… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
(7 reference statements)
1
4
0
Order By: Relevance
“…This heritage and cultural value space components make provision for compartment that could be used for self-isolation when the need arises. Findings agree with Lim (2019), Mydin et al (2014), Zwain and Bahauddin (2017), and Lim (2019) found that Late 'Straits' Eclectic Style, a type of traditional shophouses is slowly diminishing in George Town with new trend of globalization influence and modernity. Mydin et al (2014) and Zwain and Bahauddin (2017) found that many traditional shophouses courtyards in George Town Heritage City have been subjected to modifications, alterations, and deterioration. "…”
Section: Theme One: Possible Factors Impeding Observation Of Precautisupporting
confidence: 86%
“…This heritage and cultural value space components make provision for compartment that could be used for self-isolation when the need arises. Findings agree with Lim (2019), Mydin et al (2014), Zwain and Bahauddin (2017), and Lim (2019) found that Late 'Straits' Eclectic Style, a type of traditional shophouses is slowly diminishing in George Town with new trend of globalization influence and modernity. Mydin et al (2014) and Zwain and Bahauddin (2017) found that many traditional shophouses courtyards in George Town Heritage City have been subjected to modifications, alterations, and deterioration. "…”
Section: Theme One: Possible Factors Impeding Observation Of Precautisupporting
confidence: 86%
“…The architectural aspect is critical to consider when making any decision regarding adaptive reuse. The architectural style for heritage buildings including openings, colors, uses of materials [58], must be preserved to respect the prior (artistic) workmanship, features, and historical values [59]. Architectural features including building facade, interior items, finishing.…”
Section: Analysis Of Criteria Rankingmentioning
confidence: 99%
“…These components are needed to investigate and sustain the device and characteristics of these elements for traditional courtyard eclectic style shophouses regarding the role of architectural formation design components, and how this can sustain the place identity of the Straits Chinese in the shophouses. Several scholars, for example, Ahmad (2005), Kamal et al (2008), Eshak (2011), Mohamad (2011), Tharazi (2011, Sodangi et al (2013), Mydin et al (2014), Tan (2019), Khoo and Lim (2019), among others confirmed that despite the enactment of the National Heritage Act, followed by the established National Heritage Department and coupled with the existence of many heritage trusts and legislations regarding heritage conservation in Malaysia, maintenance practices for conserving heritage buildings seem to remain weak. The latter authors found that George Town is facing a critical situation with inadequate conservation manpower to maintain the city's tangible heritage.…”
Section: Place Identity In House Environmentmentioning
confidence: 99%
“…Teoh (2015) found that in Singapore, the urbanization of Straits Chinese history has lessened the influence of blending Western modernization with Southeast Asian cultural and heritage values. In George Town World Heritage Site (GTWHS), Malaysia, many of traditional shophouses facades modifications, alterations and deterioration have become a source of concern to the Penang people (Mydin et al , 2014). The authors found that among the six shophouses analysed within George Town, Malaysia, building owners are concerned with the interior whilst the exterior including the facades is ignored or modified with modern facilities without cognisance of the traditional features that defined the place identity of the people.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation